The vertical imagination and the crisis of transatlantic modernism - Haacke, Paul (Oxford University Press, 2021)
From the invention of skyscrapers and airplanes to the development of the nuclear bomb, ideas about the
9780198851448
Keywords: Literary studies: fiction; novelists & prose writers; Film theory & criticism; History of architecture; Film; Höhe; Moderne; Architektur; Literatur